2015
DOI: 10.1002/chem.201502160
|View full text |Cite
|
Sign up to set email alerts
|

A Striking Case of Enantioinversion in Gold Catalysis and Its Probable Origins

Abstract: The cyclization of the hydroxy-allene 2 to the tetrahydrofuran 3 catalyzed by the gold-phosphoramidite complex 1, after ionization with an appropriate silver salt AgX, is one of the most striking cases of enantioinversion known to date. The major reason why the sense of induction can be switched from (S) to (R) solely by changing either the solvent or the temperature or the nature of the counterion X is likely found in the bias of the organogold intermediates to undergo assisted proto-deauration. Such assistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 63 publications
2
18
0
1
Order By: Relevance
“…However, some previous studies demonstrated through kinetic analyses and calculations that the origin of solvent‐dependent stereodiscrimination was often controlled by an enthalpy–entropy compensation . Regarding gold‐catalysed enantiodivergent reactions, solvent, temperature or counterion proved to induce the enantioinversion alone or in combination with one another . Herein, we report the first silver‐ and solvent‐dependent enantiodivergent gold(I)‐catalysed reaction.…”
Section: Introductionmentioning
confidence: 99%
“…However, some previous studies demonstrated through kinetic analyses and calculations that the origin of solvent‐dependent stereodiscrimination was often controlled by an enthalpy–entropy compensation . Regarding gold‐catalysed enantiodivergent reactions, solvent, temperature or counterion proved to induce the enantioinversion alone or in combination with one another . Herein, we report the first silver‐ and solvent‐dependent enantiodivergent gold(I)‐catalysed reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[30] Based on this rationale,w es tarted to screen chiral gold complexes with the hope of finding am atching substrate/ catalyst pair. [31,32] In fact, the cationic species derived from the dinuclear Biphep complex (R)-39 and 2A gSbF 6 [33] was not only able to overcome the inertia of the substrate but provided the desired enol acetate 34 in aw ell reproducible yield of no less than 91 %. This excellent outcome met our expectation that the gold catalyzed [3,3]-sigmatropic rearrangement should be faster than the attack of the C11ÀOH group onto the resulting allenyl acetate of type B across the macrocyclic perimeter (Scheme 5).…”
Section: Methodsmentioning
confidence: 99%
“…The acyclic TADDOL‐based phosphoramidite–gold complex [{( S , S , S ,S)‐ L19 }AuCl], with 2‐naphthalenyl substituents, developed by Fürstner and co‐workers showed excellent performance in the intramolecular hydroalkoxylation of γ‐hydroxy allene and converted 156 a into the corresponding annulation product 157 a in high yield (93 %) with excellent enantioselectivity (96 % ee ; Scheme ) . Somewhat surprisingly, the best result was obtained in EtOH as the solvent, which did not outperform the attack of the tethered hydroxy group onto the allene moiety.…”
Section: Cyclization Of C−c Multiple Bonds With Tethered Nucleophilesmentioning
confidence: 99%